The Impact Of The Organization Of Operation And Maintenance Of Agricultural Equipment On The Quality Of Equipment - Khojimatov A.A. (Global Scientific Publishing, 2025)
This article discusses the types of seasonally used agricultural machinery and the importance of proper organization of their storage and maintenance in increasing the service life of the equipment. Separate storage requirements are established for each type of equipment. The degree to which storage requirements are met will lead to a decrease in the number of failures (breakdowns) of equipment during operation. As the number of failures increases, work efficiency decreases and operational performance decreases
Keywords: Machine; Mechanism; Repair; Equipment